Egg production and blood cholesterol of layers fed after adding fragrant pandan leaf flour (Pandanus amarylifolius Roxb.) - Jein Rinny Leke; E. Wantasen; J. Laihad; E. Pudjihastuti; A. Podung; R. Siahaan (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
This study aimed to determine the performance of eggs and blood cholesterol of laying hens fed with fragrant pandan leaf flour (Pandanus amarylifolius Roxb). A total of 200 laying hens were used in the study, with 5 treatments and 5 replications, each filled with 8 chickens. The research design used was completely randomized (CRD), and further analysis was conducted using Duncan's Multiple Range Test. Treatments given fragrant pandan flour were 0%, 1%, 2%, 3%, and 4%. This research was conducted for 8 weeks. Parameters included: ration consumption (g/head), ration conversion, egg weight (g), Hen Day Production (%), blood cholesterol (mg/ml), blood HDL (mg/dl) and blood LDL (mg/dl). Results showed that the use of fragrant pandan leaf flour up to 4% gave a very significant effect (P < 0.01) on conversion, hen day egg weight production, blood cholesterol, blood HDL, and blood LDL, but not significantly different (P > 0.05) on ration consumption. The study concluded that using up to 4% of fragrant pandan leaf flour increases egg production and reduces ration conversion, blood cholesterol, blood HDL, and blood LDL of laying hens and ration consumption and does not cause negative effects on the laying hens.